Da costela de Adão: o recalque e a negativação do feminino em nossa cultura e psicanálise - Farias, Ana Maria Amorim de (2005)
The aim of this work is to reflect how female repression and negativization occur in our culture and in psychoanalysis. To reach this goal, I used the historical knowledge about the cult of the Great Goddess, all the cults related to sacred prostitution, the change of the vision of the magic world when human being lived nature as a continuum of himself. There was still no separation between sacred and profane, the passage to the subjugation of the goddess by gods and heroes until the conception of the individual and the consolidation of the Jewess-Christian monotheism. Within the psychoanalysis scope we will go through femininity and feminine concepts, according to Freud s reading, a lacanian theory about the other jouissance and Winnicott s formulation of the feminine element. Feminine, in this work, refers to the human dimension present in both men and women, but since inside and out of the psychoanalysis scope supperposition of woman and femininity to feminine has occurred, I will try to elucidate the fact. The way to deal with feminine and masculine dimension made in each historical moment, crosses and is crossed by the search of the meaning in the fundamental questions of the human condition: birth and maintenance of life, death, sex, the difference represented by the other and the transcendence search. I looked for the comprehension of the feminine with the objective of determining the importance of revalorization of life in communion and new ways of thinking and living the theory and the clinic, the human relationship and self dimension